Rancang Bangun Sistem Informasi Kepegawaian (Studi Kasus PKIS Sekar Tanjung Pasuruan) - Wafi, Rokhmad Fadhlul; Wurijanto, Tutut; Soebijono, Tony (Jurnal JSIKA, 2013)
Pusat Koperasi Industri Susu –(PKIS) in Sekar Tanjung provides service of processing fresh milk into ultra high temperature (UHT) milk. In its production, PKIS Sekar Tanjung mostly serving services of milk processing for other companies such as: Latitude Visikusuma, Green Field, Garuda Food, Indolakto, Danone and Kalbe Farma. PKIS Sekar Tanjung have approximately 604 employees in production section. With the large number of employees, PKIS Sekar Tanjung can not be separated from the problem of human resources (HR). Until this days, the entire data processing was done manually using a simple application. That condition make the possibility of an error while processing data which is caused by error before recording becomes high. That condition also prolong the time needed for organizing the report. To overcome the problem of processing employees data , PKIS Sekar Tanjung need to apply the employee information system that will support the activities of Human Resource section. With the application of employee information systems, it’s expected that this system can assist Human Resource section in delivering the required information quickly.